PENGARUH MEDIA MASSA DAN PENGENDALIAN INTERNAL TERHADAP RISIKO FRAUD - Tyagita Dianingtyas Sudibyo; Riffani Rina Yanwar (LPPM Universitas Sains dan Teknologi Komputer, 2021)
Technology and growth sophistication makes the transparency process stronger and provide opportunities for fraud actions. The actions of fraud include misuse of assets, corruption, fraud of financial statements and others. Fraud's actions are all the bolds of violations, fraud, fraud and embezzlement that violate the law. This study aims to determine the influence between mass media and internal control of the risk of fraud on the kud makmur tani. This type of research uses quantitative research. Sampling using saturated sampling techniques. This research data is primary data in the form of questionnaires taken directly. The number of 32 respondents consisted of leaders and employees at KUD Tani Makmur. Data analysis uses pls-sem using SmartPLS 3.0. The significant value (P) used is 0.05. The results of the study, namely (1) the mass media has a significant positive effect on the risk of fraud with a value of p-values 0,000 (2) internal control has a negative effect on no significant risk of fraud with a value of p-values 0.038.